A broadband yellow Yb2+-doped oxynitride phosphor for high-performance white light-emitting diodes. Issue 19 (22nd August 2022) - Lv, Ying; Li, Yunkai; Fan, Siting; Chen, Changjian; Cai, Yuting; Xu, Hai; Xie, Rong-Jun
Abstract : A broadband, efficient and stable yellow (Ba, Sr)Si3 Al3 O4 N5 :Yb 2+ phosphor shows promising applications in single-phosphor-converted warm w-LEDs. Abstract : Here, we report a yellow phosphor (Ba, Sr)Si3 Al3 O4 N5 :Yb 2+, which not only has an ultra-high internal quantum efficiency of 86.9% and a full width at half maximum of 146 nm (4712 cm −1 ), but also shows superior water resistance and thermal stability. The thermal quenching activation energy of the optimized Ba0.5 Sr0.4 Si3 Al3 O4 N5 :0.1Yb 2+ phosphor was determined to be 0.25 eV. By combining a 450 nm chip with (Ba, Sr)Si3 Al3 O4 N5 :Yb 2+, a single-phosphor-converted warm white light-emitting diode with CIE chromaticity coordinates of (0.3289, 0.3539), a correlated colour temperature of 5650 K and a colour rendering index of 80 under a driven current of 150 mA was successfully fabricated. A high temperature aging test demonstrated the excellent luminous efficacy (98.5%@288 h) and CIE chromaticity coordinate stability of the white light-emitting diode.